Applying Fishbowl Strategy to Enhance Student’s Reading Comprehension Skill - Rachmanita Rachmanita (International Journal of English and Applied Linguistics (IJEAL), 2022)
Reading is essential for students' information development. Despite this, learners occasionally struggled to understand the report text. As a result, the point of the study was to ascertain whether it was a difference in reading achievement between students who used the fishbowl strategy and those who did not. All eleventh-graders from SMAN 04 Kayuagung participated in the study. Two classes consisting of 64 students were chosen utilizing a technique of purposive sampling. A quasi-experimental design was used in this research. A t-test was used to examine the data. The findings revealed that the experimental group's average post-test score (67.56) was better than the control group’s (53.22). The outcome of the t-obtained was greater than the t-table. It meant that there was a significant difference in students' Reading comprehension achievement after using the fishbowl strategy. Alternatively, the fishbowl strategy might enhance students’ reading comprehension skills of report text at SMAN 04 Kayuagung.